Bayesian networks to study the influence of teacher evaluation on the academic performance of students of the Faculty of Engineering and Architecture of a confessional private university - Loaiza Jara, Omar L. (2016)
This research aims to study the influence of the dimensions of the teaching evaluation in the academic performance of the students of the Faculty of Engineering and Architecture. The dimensions of the independent variable are based on instruments of academic management, the unit of analysis (the own Faculty) used every six months, these are: ethical-social aspect, teaching professional performance and spiritual aspect. In addition, they are based on the model of The Philosophy of Seventh-day Adventist Education, supported by Edward M. Cadwallader. The problem being addressed is to know what are the scenarios resulting from therelationships of both variables to support the administration of the Faculty in the decisions arising from these scenarios. This study is descriptive, experimental, correlational and transversal type. Can find the theorisation of the study variables, the formulation of the causal model and Bayesian, results of the resulting scenarios, as well as conclusions